THE USE OF DISCOVERY LEARNING METHOD TO IMPROVE STUDENTS’ WRITING DESCRIPTIVE TEXT - Sobari, Mochamad Roni; Husnussalam, Hendra (IKIP Siliwangi, 2019)
The direction of the research is to prove whether the discovery learning method can improve the students competence in writing descriptive text or not. The subject is the tenth grade students of MA Nurul Hidayah Batujajar which consist of 16 students. The researcher conducted 2 cycles of classroom action research as the research method. Each cycle comprised pre-test, two meetings for treatment and post-test. In collecting data, the researcher used test and non-test. From the data taken, the result tends to be satisfied. During teaching learning process, the students tend to become active participants. The results of the research showed that the students are more confident in writing descriptive text and know what to write. Furthermore, there are some improvements in their test scores which are the mean score of post-test1 in cycle one (5.65) is higher than the mean score of pretest (4.03) and the mean score of post-test2 in cycle two (6.72) is higher than the mean score of post-test1 in cycle one. From the results of the research, it can be summarized that using discovery learning method can improve the students’ writing descriptive text.